Risk Mangement Study of Solid Waste Disposal Construction Project to Improve Project Performance(Case Study: 2 X 1000 Steam Power Plant Project) - Munawar, Mufid; Sukarsono, Bambang Purwanggono; Saptadi, Singgih (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
The construction project of a coal-fired steam power plant, of course, takes into account the problem of waste (coal ash), therefore it is necessary to plan for a place to store solid waste remaining from combustion (Solid Waste Disposal). Disposal of solid waste is a useful waste storage area to prevent pollution to the surrounding environment. The construction of solid waste disposal consists of embankments and ponds, in its construction it is necessary to consider the risks that will occur, so as to minimize the impact that will be caused, in terms of cost, time and quality. This study aims to determine the extent to which risk management is applied in the implementation of solid waste disposal development projects. The survey was conducted through interviews using a likert scale (1-5) questionnaire. The population and study sample taken are contractors and subcontractors who work on solid waste disposal projects, and already had long experience with soil works. The respondents consisted of project managers, construction managers, supervisors, surveyors, quality controls, engineers, and staff involved in them. A combination of proportional and purposive sampling method was used. SEM (Smart PLS) was used to test the validity and reability of the model as the data analysis technique. The research concludes that the performance projects of solid waste disposal were influenced by resources, which influenced by managerial aspect, that that the management of manpower and materials has a major role in improving performance is key mainly.